Aplikasi Penggunaan Listrik PLN Sebagai Media Alternatif Pembelajaran Fisika Berbasis GUI MATLAB - Nugraha, Alpi Mahisha; Nurullaeli, Nurullaeli (Navigation Physics : Journal of Physics Education, 2024)
The introduction to electricity is initiated as early as elementary school, yet it remains a challenging subject despite its practical relevance. The inefficient management of electricity consumption in Indonesian households reflects a widespread lack of understanding in this area. Thus, there is a pressing need for an application to assist users in analyzing their daily electricity usage, promoting more effective management and potentially reducing household expenses. A MATLAB Graphical User Interface (GUI) application is proposed to facilitate users in managing their electricity consumption from providers such as the State Electricity Company (PLN), aiming for optimal utilization. Furthermore, this application could serve as a straightforward educational tool, particularly for physics students, aiding in the comprehension and practical application of electrical concepts in everyday life.